25 Years of Dividend Policy Research in Indonesia (1998-2023): A Bibliometric Perspective - Faldesiani, Riske; Ciptagustia, Annisa; Purnomo, Budi Supriatono; Purnamasari, Imas; Firmansyah, Egi Arvian (Universitas Pendidikan Indonesia, 2024)
This study presents a comprehensive bibliometric analysis of dividend policy literature spanning the past twenty-five years (1998–2023), with a specific focus on Indonesia. Employing advanced computational mapping techniques using Biblioshiny and VOS Viewer, the research analyses 948 relevant Scopus-indexed articles and seminar papers. Key search terms included “dividend policy,” “dividend payout ratio,” and “dividend puzzle.” Articles specifically addressing